2022
DOI: 10.3390/app12189392
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Predicting the Usage of Shared Electric Scooter Services on University Campuses

Abstract: Electric vehicles (EVs) have been progressing rapidly in urban transport systems given their potential in reducing emissions and energy consumptions. The Shared Free-Floating Electric Scooter (SFFES) is an emerging EV publicized to address the first-/last-mile problem in travel. It also offers alternatives for short-distance journeys using cars or ride-hailing services. However, very few SFFES studies have been carried out in developing countries and for university populations. Currently, many universities are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…The study's findings highlighted the model's superior predictive ability, with factors like time of day and the density of Points of Interest (POIs) being highly significant. [79] conducted a study focusing on the use of e-scooters among students and staff on campus. They also employed the Random Forest model, achieving high accuracy in predicting e-scooter usage frequency.…”
Section: Demand Prediction Studies Of E-scootersmentioning
confidence: 99%
“…The study's findings highlighted the model's superior predictive ability, with factors like time of day and the density of Points of Interest (POIs) being highly significant. [79] conducted a study focusing on the use of e-scooters among students and staff on campus. They also employed the Random Forest model, achieving high accuracy in predicting e-scooter usage frequency.…”
Section: Demand Prediction Studies Of E-scootersmentioning
confidence: 99%
“…In addition to the above-mentioned study by Zhang et al (2021), there are some studies that focused on university students' use of micromobility, particularly e-scooters. One of them is carried out by Moosavi et al (2022), who identified eleven factors that can affect the e-scooter use of university students' and staff. The factors are daily travel patterns on campus, availability of green space and water, age, road surface quality, daily travel time and cost on campus, monthly income, private vehicle ownership, connected roads, transportation to and from campus, and gender.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Safety is one of the most important factors that prevents students from riding e-scooters. Those who think e-scooters are unsafe would never ride e-scooters (Moosavi et al, 2022). E-scooters have even been banned on some university campuses, claiming they are unsafe and cause too many accidents (Abdulahi, 2022).…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation